Journal: Coal Creek rebirth: Just add explosives - Michael Milstein (International Society of Explosives Engineers, 2010)
Northwest Research Station said as more and more older dams are removed to benefit fish, it’s become clearer that rivers rework themselves quickly.“Where the dam is relatively small, it’s a quick response,” he said. “The river quickly forgets.”